China's Declining Business Dynamism - Cerdeiro, Diego; Ruane, Cian. (Washington, D.C. : International Monetary Fund, 2022)
After impressive growth in the 2000s, China's productivity has more recently stagnated. We use firm-level data to analyze productivity and firm dynamism trends from 2003 to 2018. We document six facts that together show a decline in China's business dynamism. We show that (i) the revenue share of young firms has declined, (ii) the life-cycle growth of young firms relative to older incumbents has slowed, (iii) weaker life-cycle growth can be explained by slower productivity growth and weaker investment in intangibles, (iv) younger and smaller firms are more capital constrained than their older and larger counterparts, (v) the responsiveness of capital growth to the marginal product of capital has declined, and (vi) large productivity gaps between SOEs and private firms persist. We find that business dynamism is weaker in provinces where SOEs account for a larger share of the capital stock. Our results suggest that declining private business dynamism is an important factor in explaining China's sluggish TFP growth and that SOE reform could boost productivity growth indirectly by stimulating business dynamism.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Aggregate Productivity; Cross-Country Output Convergence; Macroeconomic Analyses of Economic Development; Measurement of Economic Growth; Total Factor Productivity, Growth and Business Dynamism